Improving the effectiveness of the Henderson instruction safeguard against unreliable eyewitness identification. Issue 2 (7th February 2018) - Jones, Angela M.; Penrod, Steven
ABSTRACT: Eyewitness identifications made under poor witnessing or identification conditions have resulted in numerous wrongful convictions [National Registry of Exonerations. (2017). Retrieved January 28, 2017, fromhttp://www.law.umich.edu/special/exoneration/Pages/ExonerationsContribFactorsByCrime.aspx ]. These wrongful convictions have persuaded some courts to seek ways to improve admissibility standards concerning eyewitness identifications and jurors' ability to discern the quality of identifications. New Jersey recently ruled that case-specific instructions must be presented to the jury to determine the reliability of an identification [ New Jersey v. Henderson, 27 A.3d 872 (2011)]. Research suggests the original format of these instructions is ineffective [Dillon, M., Jones, A.M., Bergold, A.N., Hui, C., & Penrod, S. (2017). Examining the effectiveness of the Henderson eyewitness instructions. Journal of Forensic Psychology Practice . doi:10.1080/15228932.2017.1235964 ; Jones, A.M., Bergold, A.S., Dillon, M., & Penrod, S. (2017). Sensitizing jurors to factors influencing the accuracy of eyewitness identification: Assessing the effectiveness of the Henderson instructions. Journal of Experimental Criminology . doi:10.1007/s11292-016-9279-6 ]. Other studies have found one form of eyewitness instructions sensitized jurors to problematic police procedures [Pawlenko, N. B., Safer, M. A., Wise, R. A., & Holfeld, B. (2013). A teaching aid for improving jurors' assessment of eyewitness accuracy. Applied Cognitive Psychology, 27, 190–197], but no studies have found sensitivity to poor witnessing conditions. Therefore, the current study sought to modify Henderson instructions to improve sensitivity to variations in estimator variables. Jury-eligible community members read a trial transcript and rendered a verdict. Results indicated modified Henderson instructions increased sensitivity to estimator variables above and beyond a no-eyewitness-instruction control condition, while original Henderson instructions did not affect jurors' decision making. Mounting evidence suggests original Henderson instructions are ineffective and may serve to induce confusion among jurors. However, more research is needed before courts consider this revised instruction.